SEROVAR PROFILE AND DETECTION OF INVA VIRULENCE GENE AMONG NON-TYPHOIDAL SALMONELLAE SEROVARS ISOLATED FROM ACUTE GASTROENTERITIS CASES IN COASTAL KARNATAKA, SOUTHERN INDIA - Bangera, Sohan; Umakanth, Shashikiran; Bhat, Ram; Kamath, Asha; Ballal, Mamatha; Mukhopadhyay, Asish Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: Non-typhoidal salmonellosis is one of the leading zoonosis in the world caused by non-typhoidal Salmonella (NTS). Invasive infections with NTS serovars occurs due to the presence of virulence genes like invA along with the immunosuppressive conditions of the patient. The study was conducted to isolate and identify the NTS serovars and their antimicrobial resistance profile from patients with diarrhea and also to detect the virulence marker â€“ invA gene among these NTS serovars. Methods: A prospective cross-sectional study was conducted from January 2015 to December 2016 at the Enteric Diseases Division, Kasturba Medical College, Manipal. 1218 fecal specimens were collected from patients with diarrhea and before antibiotic treatment. NTS serovars were identified, serotyped and then screened for the presence of invA virulence gene. Results: A total of 33 (2.7%) NTS was isolated. Salmonella typhimurium (33.34%) was predominant followed by Salmonella oslo (30.3%). Out of 33 NTS, invA was positive for 28 isolates (84.8%) of which 25 (89.3%) patients were febrile which was statistically significant (p=0.000). Conclusion: Non-typhoidal salmonellosis is an emerging global infection among immunocompromised patients. Our study showed an association between the invA gene and febrile illness among the patients suffering. Thus, this study highlights the importance of invA as a significant marker for bloodstream invasion.